Understanding internet ethics through UCC production and teaching method for everyday practice - Kim, Jongwan; Kim, Hee-Jae; Kim, Soon-Cheol (International Journal of Engineering and Technology, 2019)
In order to effectively teach Internet ethics classes to students, we have incorporated several internet ethics videos in the class. Since the latest video presentation and its discussion were performed, it was helpful for students to recognize widespread internet ethical issues. However, simply passive video watching is insufficient in terms of improving student learning outcome to enable students to apply proper internet ethics in real life. In this work, two or three students teamed up to produce a UCC about internet ethics. Team project teaching methods are effective in not only engaging students to actively participate in class, but also to understand important concepts by producing videos themselves. Through this project, the student can reflect on his/her ethical attitude in everyday life and learn how to improve it. In addition, as a result of learning mutual copyright verification through the assignment, the possibility of copyright infringement is lowered and the burden on instructors to perform fair evaluations is reduced. Through the questionnaires on the students, we have confirmed that the UCC project teaching method is effective for studentsâ€™ understanding and real-life application of internet ethics.Â